CoreView: fresh tissue biopsy assessment at the bedside using a millifluidic imaging chip. Issue 7 (25th February 2022) - Cooper, David J.; Huang, Chuqin; Klavins, Dylan A.; Fauver, Mark E.; Carson, Matthew D.; Fereidouni, Farzad; Dintzis, Suzanne; Galambos, Csaba; Levenson, Richard M.; Seibel, Eric J.
Abstract : Our CoreView millifluidic chip features sequential modules for biopsy removal (1), transport (2), staining (3), optical imaging (3), storage (4), segmentation (5), and removal (6). This can be used in histopathology and tissue adequacy applications. Abstract : Minimally invasive core needle biopsies for medical diagnoses have become increasingly common for many diseases. Although tissue cores can yield more diagnostic information than fine needle biopsies and cytologic evaluations, there is no rapid assessment at the point-of-care for intact tissue cores that is low-cost and non-destructive to the biopsy. We have developed a proof-of-concept 3D printed millifluidic histopathology lab-on-a-chip device to automatically handle, process, and image fresh core needle biopsies. This device, named CoreView, includes modules for biopsy removal from the acquisition tool, transport, staining and rinsing, imaging, segmentation, and multiplexed storage. Reliable removal from side-cutting needles and bidirectional fluid transport of core needle biopsies of five tissue types has been demonstrated with 0.5 mm positioning accuracy. Automation is aided by a MATLAB-based biopsy tracking algorithm that can detect the location of tissue and air bubbles in the channels of the millifluidic chip. With current and emerging optical imaging technologies, CoreView can be used for a rapid adequacy test at the point-of-care for tissue identification as well as glomeruli counting in renal core needle biopsies.